The Impact of The Pandemic on The Economy of The Republic of Uzbekistan - Tursunbaevich, Baykhonov Bahodirjon; Bulturbayevich, Mullabayev Baxtiyarjon; Rahmat, Abdul (Aksara: Jurnal Ilmu Pendidikan Nonformal, 2021)
In recent years, a number of radical reforms aimed at liberalizing the socioeconomic spheres of the country have been consistently carried out. In particular, a number of reforms aimed at liberalizing the foreign exchange market, tax reform aimed at increasing incomes and stimulating production, the gradual transition to medium term budget planning, reducing the role of inflation targeting in the economy, gradual privatization of state enterprises and the introduction of market mechanisms continue.